1993
DOI: 10.1098/rsta.1993.0123
|View full text |Cite
|
Sign up to set email alerts
|

Protein structures and complexes: what they reveal about the interactions that stabilize them

Abstract: The rapid increase in the number of high-quality protein structures provides an expanding knowledge resource about interactions involved in stabilizing protein three-dimensional structures and the complexes they form with other molecules. In this paper we first review the results of some recent analyses of protein structure, including restrictions on local conformation, and a study of the geometry of hydrogen bonds. Then we consider how such empirical data can be used as a test bed for energy calculations, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…12 The electrostatic contribution to the intermolecular forces, which is the classical Coulombic interaction between the undistorted charge distributions of the molecules, dominates the intermolecular interaction at long range and generally determines the orientation dependence of the intermolecular potential in the van der Waals contact region. This was shown by the ability of an Ž accurate distributed multipole representation of .…”
Section: Ing Of CLmentioning
confidence: 99%
“…12 The electrostatic contribution to the intermolecular forces, which is the classical Coulombic interaction between the undistorted charge distributions of the molecules, dominates the intermolecular interaction at long range and generally determines the orientation dependence of the intermolecular potential in the van der Waals contact region. This was shown by the ability of an Ž accurate distributed multipole representation of .…”
Section: Ing Of CLmentioning
confidence: 99%
“…These results could be called in to question by the work of Thornton et al, which suggests that all-atom models are insufficient for the modeling of the interactions of phenol. In their work on the interactions between phenol and a carboxylate group, they found that a model constructed using distributed multipole analysis 41 outperformed the CHARMM 42 force field, suggesting that higher-order multipole moments are required in order to model accurately even those aromatic compounds that possess a dipole moment.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly we expect molecules with N−H and CO functional groups to form strong hydrogen bonds in crystals, with the classification “strong” implying that the hydrogen bond is dominated by the electrostatic interaction and the N···O separation is less than the sum of the van der Waals radii. Such hydrogen bonds typify the term, and their reliable formation, strength, and directionality are central to understanding biological structures and strategies in crystal engineering. There has been considerable research effort on defining hydrogen bonds and quantifying , their strength since Etter published general rules for hydrogen bonds as design elements in organic chemistry, and it is clear that CO and N−H are among the donors and acceptors to which these rules are expected to apply. The first rule, that “all good proton donors and acceptors are used in hydrogen bonding”, is so reliable that although exceptions have long been known, particularly for acceptors, they are sufficiently rare as to deserve comment .…”
Section: Introductionmentioning
confidence: 99%